Recall of Affective Responses to Exercise: Examining the Influence of Intensity and Time - Slawinska, Malgorzata Maria; Davis, Paul Anthony (Frontiers in Sports and Active Living, 2020)
Affective responses to exercise are noted to be dynamic and frequently vacillate between positive and negative valence during physical activity. Recalled affect following exercise can influence anticipated affective responses to exercise and guide future behaviors. Research examining affective memory processes indicates that the recall of an experience can substantially differ from the actual experience and change over time. Grounded in the dual mode model (Ekkekakis, 2003), this study examines individuals' recall of exercise-related affect over a period of 2 weeks. Forty-two adults (26 women, 16 men; Mage = 29.64, SD = 5.69) completed two 20-min treadmill exercise trials in a randomized control crossover design; the trials were set either at a low or high exercise intensity based upon individuals' ventilatory threshold. Data analyses indicate that the affective responses to the low-intensity condition were evaluated more positively than in the high-intensity condition. Recalled affect fluctuated over a 2-week time period following both the low- and high-intensity exercise trials. A significant reduction at the 24-h recall measurement point was observed in both exercise intensity conditions. Implications for future research and health promotion interventions aiming to optimize affective responses to exercise are presented.